PELATIHAN PENULISAN SURAT DINAS PADA PERANGKAT DESA KAMPUNG WISATA TAMAN YOGYAKARTA - Rini Damayanti; Fransisca Dwi Harjanti; Kaswadi Kaswadi; Sueb Sueb; Agung Pranoto (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
The aim of training in writing official letters at the village office is to increase the understanding of village officials about writing official letters that are good and correct. This community service program activity lasts for two days, namely on September 26, 27, 2020 at the Tamansari Yogyakarta hall. The total number of village apparatus / staff who attended this official letter writing training was 25 people. Based on the preliminary survey, the spelling scores of the participants in the activity were not good, meaning that there was a need for improvement in understanding Indonesian spelling. During the training, the activity participants and the implementation team conducted a reflection and evaluation of the material presented. Thus, activity participants can compile official letters properly and correctly according to the General Guidelines for Spelling in Indonesian.